013 Lipid metabolism and body composition in frontotemporal dementia-amyotrophic lateral sclerosis spectrum: effect on survival and disease progression. Issue 6 (24th May 2018) - Ahmed, Rebekah M; Highton-Williamson, Elizabeth; Caga, Jashelle; Thornton, Nicollette; Ramsey, Eleanor; Zoing, Margaret; Piguet, Olivier; Hodges, John; Halliday, Glenda; Farooqi, Sadaf; Kiernan, Matthew C
Abstract : Introduction: Patients with Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) exhibit changes in eating behaviour that could potentially affect lipid levels and body composition. This study aimed to document changes in lipid metabolism and body composition across the ALS-FTD spectrum to identify potential relationships to eating behaviour (including fat intake), cognitive change, body mass index (BMI) and effect on survival. Methods: One hundred and twenty eight participants were recruited: 37 ALS patients, 15 ALS patients with cognitive and behavioural change (ALS-Plus), and 13 ALS-FTD, 31 behavioural variant FTD, and 32 healthy controls. Fasting total cholesterol, low density lipoprotein cholesterol (LDL), high density lipoprotein cholesterol (HDL) and triglyceride levels were measured and correlated to eating behaviour (caloric, fat intake), cognitive change, and BMI; effect on survival was examined using cox regression analyses. In a cohort of 60 patients, changes in body composition and fat deposition was examined using Dual energy X-ray absorptiometry scans (DEXA), a technique used in obesity research. Results: There was a spectrum of lipid changes from ALS to FTD with increased triglyceride (p<0.001), total cholesterol/HDL ratio (p<0.001), and lower HDL levels (p=0.001) in all patient groups compared to controls. Whilst there was no increase in total cholesterol levels, a higher cholesterol level was found to correlate with 3.25 times improved survival (p=0.031). Triglyceride and HDL cholesterol correlated to fat intake, BMI, and measures of cognition and Conclusion: A spectrum of changes in lipid metabolism and body composition has been identified in ALS-FTD, with total cholesterol levels found to potentially impact on survival. These changes were mediated by changes in fat intake, and BMI, and may also be mediated by the neurodegenerative process, offering the potential to modify these factors to slow disease progression and improve survival.